Strengthening Cultural Integration through the Reinterpretation of Islamic Values in Multicultural Education in West Papua - Ulya, Dena Izzatul (MANAGIERE: Journal of Islamic Educational Management, 2026)
This study aims to explore the strategic reinterpretation of Islamic values to strengthen cultural integration within a multicultural educational environment, focusing on Insan Mulia Integrated Islamic Senior High School in Manokwari, West Papua. The school represents an Islamic educational institution serving students from diverse ethnic and cultural backgrounds, including Papuan, Javanese, Bugis, and Minang communities. Employing a qualitative case study approach, data were collected through participatory observation, in-depth interviews, and document analysis of the curriculum and extracurricular activities. Data analysis followed the Miles and Huberman model involving data reduction, presentation, and verification. The findings reveal that the contextual reinterpretation of Islamic values not only fosters tolerance and inclusivity but also functions as a managerial strategy for establishing a harmonious and culturally adaptive school climate. This study contributes to the development of a multicultural-based Islamic education management model that is responsive to the sociocultural realities of local communities.